2023
DOI: 10.1186/s12905-023-02503-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy complications in last pregnancy and mothers’ long-term cardiovascular mortality: does the relation differ from that of complications in first pregnancy? A population-based study

Abstract: Background Women who experience complications in first pregnancy are at increased risk of cardiovascular disease (CVD) later in life. Little corresponding knowledge is available for complications in later pregnancies. Therefore, we assessed complications (preeclampsia, preterm birth, and offspring small for gestational age) in first and last pregnancies and the risk of long-term maternal CVD death, taking women´s complete reproduction into account. Data and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…We have recently shown that complications in the last pregnancy are associated with a stronger burden of CVD deaths than complications in the 1st pregnancy. 5 4. In addition to one-child mothers, the risk should be evaluated in other subgroups of women.…”
Section: Future Direc Tionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that complications in the last pregnancy are associated with a stronger burden of CVD deaths than complications in the 1st pregnancy. 5 4. In addition to one-child mothers, the risk should be evaluated in other subgroups of women.…”
Section: Future Direc Tionsmentioning
confidence: 99%
“…4 Furthermore, the order in which preeclampsia occurs in a woman's reproductive history matters. 5 Pregnancy complications in one pregnancy may be linked to other complications in a subsequent pregnancy, even complications at term. By using a woman's complete pregnancy history, it is possible to evaluate the association between preeclampsia and long-term CVD mortality by the pattern of occurrence of HDP, 6 as well as other complications, in later pregnancies.…”
mentioning
confidence: 99%
“…Both SGA and large for gestational age (LGA) are being discussed as risk factors for the growing child and adult life (10). There is increasing evidence that preterm birth, preeclampsia, and abnormal fetal growth increase the risk for maternal cardiovascular disease later in life (11).…”
mentioning
confidence: 99%